2015
DOI: 10.1111/1365-2656.12323
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant predation on parasites is highly variable but constrains the ways in which parasites contribute to food web structure

Abstract: Summary Previous analyses of empirical food webs (the networks of who eats whom in a community) have revealed that parasites exert a strong influence over observed food web structure and alter many network properties such as connectance and degree distributions. It remains unclear, however, whether these community‐level effects are fully explained by differences in the ways that parasites and free‐living species interact within a food web.To rigorously quantify the interrelationship between food web structure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 67 publications
(169 reference statements)
1
45
1
Order By: Relevance
“…Previous work found that food webs including concomitant links deviated in motif frequencies [14,18]. However, motifs and niches describe the network at fundamentally different levels, and so there is no conflict between such observations and our results.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Previous work found that food webs including concomitant links deviated in motif frequencies [14,18]. However, motifs and niches describe the network at fundamentally different levels, and so there is no conflict between such observations and our results.…”
Section: Discussioncontrasting
confidence: 61%
“…showed that parasites have unique structural roles compared to free-living species: when concomitant links were excluded, parasites have diverse roles similar to freeliving consumers that have both predators and prey (i.e., intermediate taxa), but when concomitant links were included, their roles were more constrained and different [18]. This study also found that concomitant links represent the most structurally diverse type of interaction.…”
Section: Fig 2 Interaction Typesmentioning
confidence: 58%
“…(39) used network approaches to show that co-infecting parasites of humans were organized into dense clusters around distinct locations in the body (e.g., organs) and tended to interact with each other via shared resources within the host, rather than via the immune system. Similar approaches have been applied across other scales of organization–for example, to define contact pathways for transmission among individual hosts (40, 41) and to identify the role of parasites in structuring ecological food webs (42). Although the focus of network approaches thus far has often been on the patterns of links among species, emerging tools allow for more explicit examination of interaction strengths, which will help to forecast dynamic changes in the system (43).…”
Section: Approaches For Understanding Multilevel Infection Processesmentioning
confidence: 99%
“…, Dunne et al. , Cirtwill and Stouffer ). As well as affecting the free‐living community, however, many parasites rely on the free‐living food web to complete their life cycles.…”
Section: Introductionmentioning
confidence: 98%